Manusia Dan Laot: Pengetahuan Penyelesaian Sampah Masyarakat - Ramdesta, Andry; Syahrizal; Zainal Arifin (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
The waste solution that is the focus of this research is about the knowledge of the Tagaraja Village community about waste, laot and waste disposal sites so that they carry out such practices. This research uses qualitative research with an ethnographic approach. Data collection techniques are carried out through observation, interviews, documentation and literature studies. The results of the study show that the Tagaraja Village community has knowledge about how to resolve waste that can be resolved either by burning, throwing it into the laot, throwing it into the paret or just left alone, then the understanding of laot that can transport, accommodate, and decompose waste quickly makes laot a priority to be applied by the community as a way to resolve waste. The conclusion of this study shows that the knowledge of people who live in an area with various phenomena that they continue to experience has the most important role for the community in behaving, and one of them is in resolving waste. Keyword: Garbage, Knowledge About How To Deal With Garbage, Sea.